TEKNOLOGI REKLAMASI LAHAN BEKAS TAMBANG BAUKSIT MENGGUNAKAN SEEDBALL TANAMAN ADAPTIF DAN KOMPOS DIPERKAYA FABA - Putri, Aulya; Suwardi, Suwardi; Suryaningtyas, Dyah Tjahyandari; Oktariani, Putri; Widjaja, Hermanu; Randrikasari , Octaviana (Pusat Studi Pembangunan Pertanian dan Pedesaan (PSP3) dan Ilmu Pengelolaan Sumberdaya Alam dan Lingkungan (PSL), 2024)
Bauxite is one of the most mined minerals in the world and plays an important role as a raw material for aluminum production. The implementation of bauxite downstream policy has an impact on the expansion of bauxite mining area and bauxite post-mining land. The expansion of mining activities can cause an increase in the impact of environmental damage, one of which is the emergence of critical land in post-mining areas. Bauxite post-mining land often experiences problems with soil physical and chemical properties, which cause soil unable to support growth and fulfill plant nutrition needs. Alternatives that can be implemented is the use of adaptive plant seedball and Fly Ash-Bottom Ash (FABA) enriched compost utilization as ameliorant material. Post-mining land reclamation technology is the key to achieve successful reclamation and support the optimization of sustainable bauxite downstream programs in Indonesia.